Cassava mosaic disease in South and Southeast Asia: current status and prospects - Hareesh, Padinjarepulikkiyil Sankaran; Resmi, Thulasi Raveendrannair; Sheela, Madhavi N.; Makeshkumar, Thangaraj (Frontiers in Sustainable Food Systems, 2023)
Cassava is one of the most important food and industrial crops in Asia, Africa, and South America. Cassava mosaic disease (CMD), caused by cassava mosaic geminivirus, is one of the major constraints to cassava cultivation. In Asia, the disease is caused by the Indian cassava mosaic virus and Sri Lankan cassava mosaic virus. Phytosanitation, vector control, breeding, and genetic engineering strategies have been widely adopted to manage the disease. This study provides a comprehensive review of the disease spread, the development of diagnostic methods, and various approaches employed for the management of CMD in South and Southeast Asia.